An intersubjective perspective on the role of personal therapy in being a psychotherapist - Haumann, Hester Johanna (Rhodes University, Faculty of Humanities, Department of Psychology, 2005)
The purpose of this study was to explore how personal therapy influences experienced psychodynamic psychotherapists' ways of being clinicians, and, by implication, their professional development. A hermeneutic research method, which also drew upon aspects of grounded theory methodology, was therefore devised to explore and examine how personal therapy and professional practice relate to each other and to the therapist's development, and to deepen this descriptive account into a more differentiated and theoretically viable understanding. In-depth, semi-structured interviews were conducted with eight psychodynamic psychotherapists who were working as clinicians and who were concurrently in therapy. Keeping the research objective in mind, a list of questions was developed from the interview material through which the data was re-read and edited. In accordance with the aims of the study, and as suggested by the results of the initial phase of the textual analysis, intersubjective theory, mainly that of Jessica Benjamin, was used to generate a conceptual framework through which the interview material was further interpreted. This foregrounded the shifting power distributions and the varying processes of identification between the treating therapists and the participants. The Jungian notion of the wounded healer was intersubjectively reconfigured as indicating a therapist whose (often unacknowledged) needs and vulnerabilities engender a proclivity to relate to patients as objects rather than subjects. The participants could all be described as having started out their professional lives as wounded healers. The effects of personal therapy on their clinical work were conceptualised in terms of increased abilities for subject-to-subject relating. These were linked to augmented capacities for reflective and symbolic thinking and an enhanced openness to the implicit, unformulated and opaque aspects of experiences in the therapeutic space. Finally an intersubjective model of personal therapy and development as a therapist was generated. It was concluded that because of the focus on the therapeutic relationship as the vehicle for change in psychodynamic psychotherapy, as well as the current increasing emphasis on the use of the therapist's subjectivity, the therapist's capacity to engage in and sustain subject-tosubject relating and, by implication, the therapist's personal therapy, are of pivotal importance for all therapists doing the work of psychodynamic psychotherapy.
Keywords: Psychodynamic psychotherapy; Psychotherapy; Clinical psychology; Psychotherapists -- Psychology; Psychoanalysis; Countertransference (Psychology)